Programa de promoción y prevención de la salud bucodental dirigido a niños y representantes legales del grado transición del colegio Simón Bolívar sede Hernando Acevedo - Mora Ayala, Rosa Carolina; Villamizar Cruz, Luz Angela (Universidad Antonio Nariño, 2022)
This research project was primarily aimed at designing an oral health promotion and prevention program aimed especially at legal representatives and children of the transitional degree of the Colegio Simón Bolívar headquarters Hernando Acevedo. This program was created and designed so that the material produced will be in the hands of the attendants so that they can transmit the information to children as they grow, to future generations.